Accuracy of a novel stress echocardiography pattern for myocardial bridging in patients with angina and no obstructive coronary artery disease – A retrospective and prospective cohort study. (15th July 2020) - Pargaonkar, Vedant S.; Rogers, Ian S.; Su, Jessica; Forsdahl, Signe Helene; Kameda, Ryo; Schreiber, Donald; Chan, Frandics P.; Becker, Hans-Christoph; Fleischmann, Dominik; Tremmel, Jennifer A.; Schnittger, Ingela
Abstract: Background: Myocardial bridge (MB) may cause angina in patients with no obstructive coronary artery disease (CAD). We previously reported a novel stress echocardiography (SE) pattern of focal septal buckling with apical sparing in the end-systolic to early-diastolic phase that is associated with the presence of an MB. We evaluated the diagnostic accuracy of this pattern, and prospectively validated our results. Methods: The retrospective cohort included 158 patients with angina who underwent both SE and coronary CT angiography (CCTA). The validation cohort included 37 patients who underwent CCTA in the emergency department for angina, and prospectively underwent SE. CCTA was used as a reference standard for the presence/absence of an MB, and also confirmed no obstructive CAD. Results: In the retrospective cohort, an MB was present in 107 (67.7%). The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were 91.6%, 70.6%, 86.7% and 80%, respectively. On logistic regression, focal septal buckling and Duke treadmill score were associated with an MB. In the validation cohort, an MB was present in 31 (84%). The sensitivity, specificity PPV and NPV were 90.3%, 83.3%, 96.5% and 62.5%, respectively. On logistic regression, focal septal buckling was associated with an MB. Conclusion: Presence of focal septal buckling with apical sparing on SE is an accurate predictor of an MB in patients with angina and no obstructive CAD. This pattern can reliably be used to screen patients who may benefit from advanced non-invasive/invasive testing for an MB as a cause of their angina. Highlights: Focal septal buckling with apical sparing on stress echo accurately predicts an MB. This pattern can help identify an MB as a potential cause of angina. And can be useful to screen patients who may benefit from further testing for an MB.